GENNOVATE: Enabling gender equality in agricultural and environmental innovation - Elias, Marlène; Badstue, Lone B. (Bioversity International, 2017)
Presented by Marlene Elias (Bioversity International) and Lone Badstue (CIMMYT), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017